Transfer Pricing Risks in the Mining Sector: Evidence from Indonesian Tax Disputes (Indonesian Tax Justice Review, 2025)
Transfer pricing practices in the mining sector present significant risks to revenue mobilization in developing countries due to concentrated markets and limited price comparables. This paper analyzes Indonesian tax disputes involving multinational mining companies to assess the effectiveness of transfer pricing enforcement. Using doctrinal case law analysis, the study examines disputes related to related-party sales, cost allocation, and pricing of mineral exports. The findings reveal persistent information asymmetries between tax authorities and multinational enterprises, compounded by limited access to reliable comparables and technical expertise. These constraints weaken the enforcement of the arm’s length principle and reduce effective taxation of extractive profits. The paper argues that Indonesia’s experience highlights structural limitations of traditional transfer pricing methods in extractive industries. The global contribution of this study lies in providing sector-specific empirical evidence supporting calls for alternative profit allocation approaches, such as formulary or rent-based taxation. By situating Indonesian disputes within global tax justice debates, the study contributes to rethinking international tax rules for sectors characterized by high capital intensity and market concentration.